Wide-band-gap semiconductor crystal luminescent material and preparation method and application thereof
By forming a wide-bandgap semiconductor crystal luminescent material with a one-dimensional chain structure by quinolinecarboxylic acid-based ligands and cadmium ions, the problems of low luminescence efficiency, poor stability and difficulty in wavelength control of existing materials are solved, and efficient and stable red luminescence performance is achieved, which is suitable for display technology and lighting and other fields.
Patent Information
- Application Number
- CN202510950507.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-10-14
AI Technical Summary
Existing wide-bandgap semiconductor light-emitting materials have problems such as low luminous efficiency, insufficient photostability, poor thermal stability, and difficulty in controlling the luminescent wavelength.
A wide-bandgap semiconductor crystal luminescent material with a one-dimensional chain structure formed by quinolinecarboxylic acid-based ligands and cadmium ions is prepared by adjusting the ligand structure and synthesis conditions to have high-efficiency luminescence performance, good light stability and thermal stability.
It achieves efficient luminescence performance, can emit light in the red region, has good photostability and thermal stability, is suitable for a variety of luminescence application scenarios, and can precisely control the luminescence wavelength.
Smart Images

Figure CN120774940A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor luminescent materials, and in particular to a wide-bandgap semiconductor crystal luminescent material, a preparation method thereof, and applications thereof. Background Art
[0002] With the rapid development of optoelectronic technology, wide-bandgap semiconductor light-emitting materials have shown tremendous potential for applications in fields such as display technology and lighting. Wide-bandgap semiconductor materials, defined as those with a bandgap greater than 2.0 eV, are ideal for light-emitting applications due to their excellent optical and electrical properties, enabling efficient light emission and charge transport. These properties give them significant advantages in high-brightness and high-efficiency optoelectronic applications.
[0003] However, current wide-bandgap semiconductor light-emitting materials still face many technical challenges, such as low luminescence efficiency, insufficient photostability, poor thermal stability, and difficulty in controlling the emission wavelength. For example, traditional inorganic wide-bandgap semiconductor materials, such as Ga2O3, have a relatively high bandgap energy, approximately between 4.5eV and 4.9eV. This characteristic theoretically enables them to achieve short-wavelength luminescence, with potential application value in fields such as ultraviolet luminescence. However, the preparation process of Ga2O3 is complex, and its luminescence efficiency needs to be improved. While organic light-emitting materials have good flexibility and biocompatibility, their luminescence efficiency and photostability need to be further improved. Summary of the Invention
[0004] In response to the shortcomings of existing wide-bandgap semiconductor luminescent materials in terms of luminous efficiency, photostability, thermal stability and luminescent wavelength control, the present invention provides a wide-bandgap semiconductor crystal luminescent material and its preparation method and application, providing a feasible idea and solution for improving the performance of existing materials.
[0005] To achieve the above objectives, the technical solutions of the present invention are as follows.
[0006] The first aspect of the present invention provides a wide bandgap semiconductor crystal luminescent material, whose chemical composition is [CdLCl]2·H2O or [Cd2L2(Ac)(H2O)]; L represents a quinolinecarboxylic acid ligand; Ac represents an acetate ion; the crystal structure of the wide bandgap semiconductor crystal luminescent material is a one-dimensional chain structure.
[0007] The wide-bandgap semiconductor crystal luminescent material of the present invention has efficient luminescence performance, good photostability and thermal stability. By adjusting the ligand structure and synthesis conditions, the present invention can achieve precise control of the luminescence wavelength to meet the needs of different application scenarios.
[0008] The wide-bandgap semiconductor crystal luminescent material of the present invention utilizes a one-dimensional chain-like structure formed by bridging the carboxyl groups of quinolinecarboxylic acid-based ligands with cadmium ions. This crystalline complex emits light in the red region, making it a potential red luminescent material. Solid-state UV-visible diffuse reflectance spectroscopy analysis indicates that the energy band gaps of the wide-bandgap semiconductor crystal luminescent material of the present invention are 4.89 eV and 4.76 eV, respectively, making it a wide-bandgap semiconductor material.
[0009] Preferably, the minimum asymmetric unit of the crystal structure of the wide bandgap semiconductor crystal luminescent material comprises two cadmium ions, one lattice water molecule, two deprotonated quinolinecarboxylic acid ligands and two chloride ions; the two cadmium ions are located at the center of the minimum asymmetric unit, and the two cadmium ions are coordinated by four oxygen atoms and two chloride ions on the two deprotonated quinolinecarboxylic acid ligands to form a one-dimensional chain structure with a six-coordinate structure.
[0010] Alternatively, the minimum asymmetric unit of the crystal structure of the wide bandgap semiconductor crystal luminescent material comprises two cadmium ions, a deprotonated quinolinecarboxylic acid ligand, a lattice water molecule and an acetate ion; one cadmium ion is coordinated with four deprotonated quinolinecarboxylic acid ligands and two deprotonated acetate ions to form a one-dimensional chain structure with a six-coordinate structure.
[0011] Preferably, the wide bandgap semiconductor crystal luminescent material having a chemical composition of [CdLCl]2·H2O crystallizes in the triclinic system with a space group of P -1; the unit cell parameters are a =10.5862(9)Å, b =11.0361(11)Å, c =11.7883(11)Å, α =108.0495(7)°, β =110.495(7)°, γ =101.927(7)°, V =1147.2(2)Å 3 , Z=2.
[0012] The wide bandgap semiconductor crystal luminescent material with the chemical composition [Cd2L2(Ac)(H2O)] crystallizes in the monoclinic system with a space group of I2 / m ; The unit cell parameters are a =9.6626(3)Å, b =18.3594(5)Å, c =13.6664(4)Å, α =90°, β =104.515(3)°, γ =90°, V =2347.03(12)Å3 , Z=4.
[0013] Preferably, the wide bandgap semiconductor crystal light-emitting material emits light in the red region, and the color coordinate values are (0.537, 0.337) or (0.361, 0.336).
[0014] A second aspect of the present invention provides a method for preparing a wide-bandgap semiconductor crystal light-emitting material, comprising the following steps: In a solvent system, a quinoline carboxylic acid-based ligand reacts with cadmium acetate at 80 DEG C to 110 DEG C to prepare a wide-bandgap semiconductor crystal luminescent material.
[0015] Preferably, the structural formula of the quinolinecarboxylic acid-based ligand is as follows: .
[0016] Preferably, the molar ratio of the quinolinecarboxylic acid ligand to the cadmium acetate is 1:1 to 2. The cadmium acetate is cadmium acetate dihydrate.
[0017] Preferably, the solvent is a mixture of ethanol and water, and the volume ratio of ethanol to water is 1:1 to 2. Preferably, the reaction time is 3 to 7 days.
[0018] Preferably, after the reaction is completed, a cleaning step is further included, and the cleaning step mainly involves rinsing with water 3 to 5 times.
[0019] A third aspect of the present invention provides an application of a wide bandgap semiconductor crystal luminescent material in preparing a light-emitting device, wherein the wide bandgap semiconductor crystal luminescent material is the wide bandgap semiconductor crystal luminescent material described in the first aspect.
[0020] Preferably, the light emitting device is a light emitting device that emits red light. The light emitting device of the present invention includes but is not limited to light emitting devices in the fields of display technology and lighting.
[0021] Beneficial effects of the present invention: 1. The present invention mainly utilizes the carboxyl group of the quinolinecarboxylic acid-based ligand to bridge the cadmium ion to form a one-dimensional chain structure crystal complex, and the formed crystal complex is a wide-bandgap semiconductor crystal luminescent material that emits light in the red region and has efficient luminescent performance. It is suitable for a variety of luminescent application scenarios and provides a new feasible idea and solution for wide-bandgap semiconductor luminescent materials.
[0022] 2. The wide bandgap semiconductor crystal luminescent material of the present invention exhibits good light stability and thermal stability under conditions such as high temperature and light, which can extend service life and reduce maintenance costs.
[0023] 3. By adjusting the ligand structure and synthesis conditions, the present invention can achieve precise control of the luminescence wavelength to meet the needs of different application scenarios, providing a new idea and method for the development of new high-performance luminescent materials, which has important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the partial crystal structure of complex 1 in Example 1.
[0025] Figure 2 It is a one-dimensional chain diagram of complex 1 in Example 1.
[0026] Figure 3 This is a schematic diagram of the partial crystal structure of complex 2 in Example 2.
[0027] Figure 4 It is a one-dimensional chain diagram of complex 2 in Example 2.
[0028] Figure 5 These are the crystal UV-visible excitation and emission spectra of complex 1 and complex 2.
[0029] Figure 6 This is the crystal CIE1931 color coordinate diagram of complex 1 and complex 2.
[0030] Figure 7 is the crystal thermogravimetric diagram of complex 1 and complex 2.
[0031] Figure 8 is the direct optical band gap diagram of complex 1.
[0032] Figure 9 is the direct optical band gap diagram of complex 2. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0035] The technical solution of the present invention is further described below through specific embodiments.
[0036] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0037] In the following examples, the quinoline carboxylic acid ligand, referred to as L ligand, has the molecular formula of C 11 H9NO3; the chemical name is 3-hydroxy-2-methylquinoline-4-carboxylic acid. The structural formula is as follows:
[0038] .
[0039] The quinoline carboxylic acid ligand is synthesized in the laboratory, and the preparation method of the quinoline carboxylic acid ligand includes the following steps: S1, synthesis of indigo: indigo 0.5 mol, K2Cr2O7 1.0 mol, distilled water 200 mL are added into a 500 mL three-necked flask and stirred. After cooling, 250 mL of 10 wt% dilute H2SO4 is added, and stirred at 43°C for 1.5 h. After dilution with two volumes of distilled water, filtration, dissolution in a 10% NaOH solution, and neutralization to pH = 7 with a 10% HCl solution, indigo is obtained, with a yield of 116 g and a yield of 90%, and a melting point of 210°C. HRMS m / z (ESI) calculated for C8H5NO2, [M+H] + 147.0320, found 147.0826.
[0040] The structural formula of indigo is .
[0041] The structural formula of indigo is .
[0042] S2, synthesis of quinoline carboxylic acid ligand: indigo 0.5 mol and NaOH 0.5 mol are dissolved in distilled water 200 mL and filtered. The filtrate is added to chloroacetone 1.0 mol, and a 10% hydrochloric acid solution is added dropwise to adjust pH = 7, and filtered to obtain quinoline carboxylic acid ligand, with a yield of 96 g and a yield of 95%, and a melting point of 225°C. HRMS m / z (ESI) calculated for C 11 H9NO3, [M+H] + 203.0582, found 203.0548. 1 H NMR (400MHz, DMSO) δ 9.15 (s, 1H), 7.93(d, J = 8.0 Hz, 1H), 7.64 (t, J = 8.0 Hz, 1H), 7.60–7.52 (m, 2H), 2.70 (s,3H).
[0043] Example 1 A preparation method of a wide band gap semiconductor crystal luminescent material, including the following steps: The quinoline carboxylate ligand and cadmium acetate dihydrate were mixed in a solvent in a molar ratio of 1:1 to obtain a mixture. The solvent was deionized water and ethanol mixed in a volume ratio of 2:1.
[0044] The mixture was placed in a closed environment and reacted at 80°C for 7 days, and then cooled to room temperature. The crystals were collected to obtain a crude product. The crude product was washed with deionized water 3 times to obtain a wide-bandgap semiconductor crystal luminescent material. The wide-bandgap semiconductor crystal luminescent material prepared in Example 1 is denoted as complex 1.
[0045] Example 2 A method for preparing a wide-bandgap semiconductor crystal luminescent material includes the following steps: The quinoline carboxylate ligand and cadmium acetate dihydrate were mixed in a solvent in a molar ratio of 1:2 to obtain a mixture. The solvent was deionized water and ethanol mixed in a volume ratio of 2:1.
[0046] The mixture was placed in a closed environment and reacted at 110°C for 3 days, and then cooled to room temperature. The crystals were collected to obtain a crude product. The crude product was washed with deionized water 5 times to obtain a wide-bandgap semiconductor crystal luminescent material. The wide-bandgap semiconductor crystal luminescent material prepared in Example 2 is denoted as complex 2.
[0047] Test 1: structure analysis.
[0048] The wide-bandgap semiconductor crystal luminescent materials prepared in Example 1 and Example 2 were subjected to structure analysis by single crystal X-ray diffraction, and the results are shown in Figures 1 to 4 and Table 1.
[0049] Table 1 Crystallographic data of complex 1-2 Through single crystal X-ray diffraction analysis, it was determined that complex 1 and complex 2 are both one-dimensional chain structures.
[0050] As Figure 1 and Figure 2 , the chemical composition of complex 1 is [CdLCl]2·H2O, and the smallest asymmetric unit of complex 1 contains two Cd (II) ions, one lattice water molecule, two deprotonated quinoline carboxylate ligands, and two chloride ions. The two Cd (II) ions are located at the center of the smallest asymmetric unit and are surrounded by two quinoline carboxylate ligands. Overall, the two cadmium ions are coordinated by four oxygen atoms on the carboxyl groups of the two deprotonated quinoline carboxylate ligands and two chloride ions, forming a stable one-dimensional chain structure with a six-coordinated structure.
[0051] In the molecule of complex 1, a free water molecule forms a hydrogen bond with the nitrogen atom of the quinolinecarboxylic acid ligand, and the hydroxyl group of the quinolinecarboxylic acid ligand also forms a hydrogen bond with the adjacent deprotonated carboxyl group. There is a certain π-π weak interaction in complex 1, and the center-of-mass distance and translation distance are as follows: the center-of-mass distance of Cg1···Cg3 is 3.552Å, and the translation distance is 1.128Å; the center-of-mass distance of Cg1···Cg4 is 3.495Å, and the translation distance is 0.873Å; the center-of-mass distance of Cg2···Cg3 is 3.519Å, and the translation distance is 1.027Å; the center-of-mass distance of Cg2···Cg4 is 3.499Å, and the translation distance is 1.163Å; the center-of-mass distance of Cg3···Cg3 is 3.854Å, and the translation distance is 1.849Å; the center-of-mass distance of Cg3···Cg4 is 3.730Å, and the translation distance is 1.584Å, as shown in Figure 2. Figure 4 In complex 1, Cg1#C11, C10, C9, C8, C7, C6; Cg2#C22, C21, C20, C19,C18, C17; Cg3#N1, C6, C11, C2, C3, C4; Cg4#N2, C17, C22, C13, C14, C15.
[0052] like Figure 3 and Figure 4 The asymmetric unit of complex 2 contains two Cd(II) ions, a deprotonated L ligand, a lattice water molecule, and an acetate ion. The cadmium ion is connected to the deprotonated quinoline carboxylate ligand and the acetate ion. The Cd-O bond length ranges from 2.255(8)Å to 2.35(12)Å, and the Cd-OC bond angle ranges from -77.6(19)° to 180.0(5)°, which are similar to the bond angles in Cd(II) complexes reported in the literature.
[0053] There is also a certain π-π weak interaction in complex 2. The center-of-mass distance of Cg1···Cg2 is 3.528Å, and the translation distance is 0.419Å; the center-of-mass distance of Cg2···Cg2 is 3.5875Å, and the translation distance is 1.295Å. Figure 7 In complex 2, Cg1 is C6, C5, C4, C3, C2, C1; Cg2 is C1, C6, C7, C9, C10.
[0054] Test 2: Luminous performance analysis.
[0055] The photoluminescence was studied by fluorescence spectrophotometry. Figure 5 .Depend on Figure 5 The measurement results show that complexes 1 and 2 emit light in the red region and are potential red luminescent materials.
[0056] The fluorescence spectrum data were analyzed by CIE1931 software, and the color coordinates of complex 1 were calculated to be (0.537, 0.337), and the color coordinates of complex 2 were calculated to be (0.361, 0.336). Figure 6 .
[0057] Test 3: Thermal stability analysis.
[0058] Thermogravimetric analysis was used to evaluate the thermal stability of complexes 1 and 2. Figure 7 Complexes 1 and 2 experience significant weight loss around 238°C, ultimately resulting in a 29% weight loss, primarily attributable to the removal of the L ligand. Furthermore, slow weight loss occurs after 268°C, plateauing at 415°C. Slow weight loss also occurs between 500°C and 800°C. Overall, the weight loss of complexes 2, 1, and the L ligand shows a gradually increasing trend.
[0059] Test 4: Conductor performance analysis.
[0060] In order to study the optical properties of two wide-bandgap semiconductor crystal luminescent materials, the light absorption properties of complexes 1 and 2 were measured by UV-visible diffuse reflectance spectroscopy, and the conductor properties of complexes 1 and 2 were measured by UV-visible diffuse reflectance spectroscopy.
[0061] The solid-state UV-visible diffuse reflectance spectrum of complex 1 was measured at room temperature using barium sulfate as a reference, with a reflectance of 100%. The diffuse reflectance spectrum was measured in the range of 200 nm to 900 nm. The data were processed using the Kubelka-Munk function.
[0062] like Figure 8 and Figure 9 As shown, the band gap values of Complex 1 are 4.89 eV, and those of Complex 2 are 4.76 eV. The ultra-wide band gap of Ga2O3, a semiconductor material with excellent chemical and thermal stability, is between 4.5 eV and 4.9 eV. Therefore, the band gap values of Complexes 1 and 2 are comparable to that of Ga2O3. This indicates that Complexes 1 and 2 have the potential to become excellent semiconductor materials.
[0063] In summary, the wide-bandgap semiconductor crystal luminescent material prepared by the embodiment of the present application has emission light in the red region, and the color coordinate values are (0.537, 0.337) and (0.361, 0.336) respectively, and has good luminescent performance, and is suitable for various luminescent application scenarios. Moreover, the wide-bandgap semiconductor crystal luminescent material prepared by the embodiment of the present application shows good thermal stability under high temperature conditions, can prolong the service life, and reduce the maintenance cost. By adjusting the ligand structure and the synthesis conditions, the luminescent wavelength can be controlled, and the needs of different application scenarios can be met.
[0064] The above merely describes preferred embodiments of the present application, and is not intended to limit the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A wide bandgap semiconductor crystal luminescent material, characterized in that: Its chemical composition is [CdLCl]2·H2O or [Cd2L2(Ac)(H2O)]; L represents a quinolinecarboxylic acid ligand; Ac represents an acetate ion; and the crystal structure of the wide bandgap semiconductor crystal luminescent material is a one-dimensional chain structure.
2. The wide bandgap semiconductor crystal light-emitting material according to claim 1, characterized in that The minimum asymmetric unit of the crystal structure of the wide-bandgap semiconductor crystal luminescent material comprises two cadmium ions, one lattice water molecule, two deprotonated quinolinecarboxylic acid ligands, and two chloride ions; the two cadmium ions are located at the center of the minimum asymmetric unit, and the two cadmium ions are coordinated by four oxygen atoms and two chloride ions on the two deprotonated quinolinecarboxylic acid ligands to form a one-dimensional chain structure with a six-coordinate structure; Alternatively, the minimum asymmetric unit of the crystal structure of the wide bandgap semiconductor crystal luminescent material comprises two cadmium ions, a deprotonated quinolinecarboxylic acid ligand, a lattice water molecule and an acetate ion; one cadmium ion is coordinated with four deprotonated quinolinecarboxylic acid ligands and two deprotonated acetate ions to form a one-dimensional chain structure with a six-coordinate structure.
3. The wide bandgap semiconductor crystal light-emitting material according to claim 1, characterized in that The wide bandgap semiconductor crystal luminescent material with the chemical composition [CdLCl]2·H2O crystallizes in the triclinic system with a space group of P -1; the unit cell parameters are a =10.5862(9)Å, b =11.0361(11)Å, c =11.7883(11)Å, α =108.0495(7)°, β =110.495(7)°, γ =101.927(7)°, V =1147.2(2)Å 3 , Z=2; The wide bandgap semiconductor crystal luminescent material with the chemical composition [Cd2L2(Ac)(H2O)] crystallizes in the monoclinic system with a space group of I2 / m ; The unit cell parameters are a =9.6626(3)Å, b =18.3594(5)Å, c =13.6664(4)Å, α =90°, β =104.515(3)°, γ =90°, V =2347.03(12)Å 3 , Z=4.
4. The wide bandgap semiconductor crystal light-emitting material according to claim 1, characterized in that The wide bandgap semiconductor crystal light-emitting material emits light in the red region, and the color coordinate values are (0.537, 0.337) or (0.361, 0.336).
5. A method for preparing the wide bandgap semiconductor crystal light-emitting material according to any one of claims 1 to 4, characterized in that: The following steps are involved: In a solvent system, a quinoline carboxylic acid-based ligand reacts with cadmium acetate at 80 DEG C to 110 DEG C to prepare a wide-bandgap semiconductor crystal luminescent material.
6. The method for preparing a wide bandgap semiconductor crystal light-emitting material according to claim 5, wherein: The structural formula of the quinoline carboxylic acid ligand is as follows: 。 7. The method for preparing a wide bandgap semiconductor crystal light-emitting material according to claim 5, wherein: The molar ratio of the quinoline carboxylic acid ligand to the cadmium acetate is 1:1-2.
8. The method for preparing a wide bandgap semiconductor crystal light-emitting material according to claim 5, wherein: The solvent is a mixture of ethanol and water; and the volume ratio of ethanol to water is 1:1-2.
9. Use of a wide bandgap semiconductor crystal luminescent material in the preparation of a light-emitting device, characterized in that: The wide bandgap semiconductor crystal light-emitting material is the wide bandgap semiconductor crystal light-emitting material according to any one of claims 1 to 4.
10. Use of the wide bandgap semiconductor crystal luminescent material according to claim 9 in preparing a light-emitting device, characterized in that: The light emitting device is a light emitting device that emits red light.